Life-cycle savings and public policy : a cross-national study of six countries - Börsch-Supan, Axel, 1954- (Academic Press, 2003)
The key to understanding household saving is obtaining appropriate data. Dealing with differences between rich and poor households, for example, or the old and the young, require observation of a large number of households. The focus of this study is to obtain data on many households from a number of different countries and to examine them in a coherent fashion. The hope is that through these observations we can learn about the ways policies affect savings and that other differences among savers can be controlled for, instead of being blamed on "cultural differences * Features a consistent framework among chapters * Reaches a harmony between measurement and analysis to compare accurately the resulting data and statistics * Provides econometric methodology to reveal the way policies affect savings.